Sexual Behaviour Evidence and Evidence of Bad Character in Sexual Offence Proceedings: Proposing a Combined Admissibility Framework. (February 2020) - Brewis, Brian; Jackson, Adam
This article critically evaluates whether the 'rape shield' legislation in England and Wales, as currently contained in s 41 Youth Justice and Criminal Evidence Act (YJ&CEA) 1999, is fit for purpose. The article addresses the impact of the case of R v Evans (Chedwyn) [2016] EWCA Crim 452 which received a disproportionately high amount of media scrutiny and led to subsequent calls for greater restrictions on sexual behaviour evidence. The article examines possible reform proposals by Findlay Stark and Matt Thomason and the results of empirical research conducted by Laura Hoyano before proposing the introduction of a 'combined admissibility framework' for evidence of a complainant's previous sexual behaviour and bad character. The proposed framework seeks to retain the high threshold for the admissibility, in particular, of evidence relating to a complainant's previous sexual behaviour while introducing a more holistic and straightforward model moving away from the strict categories approach adopted by s 41 YJ&CEA 1999.